Efek Ekstrak Campuran Kulit Batang Pulai (Alstonia scholaris) dan Meniran (Phyllanthus niruri) pada Mencit Swiss Webster yang Diinfeksi Plasmodium berghei - Intan, Putri Reno; Winarno, M. Wien; Prihatini, Nita (Jurnal Kefarmasian Indonesia, 2016)
Pulai and meniran is one of the medicinal plants that have been studied as a possible antimalarial drugs. This study aims to evaluate the antimalarial activity of a mixture of pulai bark and meniran extracts as antimalarial drugs. Acute toxicity tests was performed using male and female Wistar rats each 25 animals with four doses of treatment. Antimalarial test using 72 mice were divided into six dose groups: group CMC, DHP, dose mixture of 1330; 443.34; 147.78 mg/kg bw and doses of pulai groups 1330 mg /kg bw. All the mice were infected with Plasmodium berghei (D0) and given the extracts orally for 14 days. Giemsa blood stainning taken on days D1-D7 and D14 were analyzed for percentage of parasitaemia, lymphocytes, monocytes and granulocytes. Results of acute toxicity test (LD50) values obtained from extract mixture was more than 14285 mg/kg bw, are classified as non-toxic materials. The most effective dose of the test antimalarial obtained from the percentage of parasites reducing and leukocytes differential, was 147.78 mg/kg. A mixture of pulai bark and meniran extract can be considered to be used as an alternative drug in the treatment of malaria. Further research is needed to isolate and characterized the active ingredients which have the effect of antimalarial to be recommended as an antimalarial drug in the future.